LEARN EARTH ROTATION AND REVOLUTION: PENGEMBANGAN MEDIA GEOROTATION UNTUK PEMBELAJARAN DIGITAL GEOGRAFI - Khotimah, Annisa Khusnul; Soelistjo, Djoko; Putra, Alfyananda Kurnia; Kristanti, Yohana Ayu (Universitas Negeri Malang, 2023)
LEARN EARTH ROTATION AND REVOLUTION: DEVELOPMENT OFGEOROTATION MEDIA FOR LEARNING DIGITAL GEOGRAPHY Learning media is an intermediary in the delivery of information through various channels. Theinformation conveyed can provide stimulation to students both in terms of thoughts, to the will thatcan improve the learning process. The use of learning media in geography can help studentsdescribe, describe, or describe things that are abstract and difficult to understand. Thisdevelopment research aims to develop a learning media in the form of applications that can beaccessed on smartphones. This development research method uses ADDIE (Analyze, Design,Development, Implementation, Evaluation). The types of data in this development research arequalitative data and quantitative data. Qualitative data were obtained from criticism andsuggestions from expert validators and trial respondents. Quantitative data in this developmentresearch is in the form of numerical scores in the questionnaire obtained from expert validatorsand trial respondents. The Georotation in this study has been tested on 36 students of class X-DSMAN 2 Probolinggo. The results of research on the development of Georotation media obtaineda percentage of 98 percent of media expert validators, 77 percent of material expert validators,97 percent of teacher responses, 83 percent of student responses as test subjects. Thus theresults show that the development of Georotation very suitable for use in learning geography. Media pembelajaran sebagai perantara untuk merangsang kemampuan berpikir peserta didikdalam proses pembelajaran. Penelitian pengembangan ini bertujuan untuk mengetahuikelayakan media pembelajaran Georotation yang dikembangkan untuk pembelajaran geografi.Desain penelitian pengembangan ini menggunakan ADD (Analyze, Design, Development),merupakan bentuk modifikasi desain penelitian ADDIE. Jenis data dalam penelitianpengembangan ini yaitu data kualitatif dan data kuantitatif. Data kualitatif diperoleh dari kritik dansaran oleh validator media, validator materi, dan responden uji coba. Data kuantitatif dalampenelitian pengembangan ini berupa skor angka dalam angket yang diperoleh dari validatormateri, validator media, dan responden uji coba. Produk Georotation pada penelitian ini telah diujicobakan kepada siswa kelas X-D SMAN 2 Probolinggo sejumlah 36 peserta didik. Hasil penelitianpengembangan Media Georotation memperoleh persentase 98 persen dari validator ahli media,77 persen dari validator ahli materi, 97 persen dari tanggapan guru, 83 persen dari tanggapanpeserta didik sebagai subjek uji coba. Dengan demikian hasil menunjukkan, bahwa pengembangan media pembelajaran Georotation sangat layak digunakan dalam pembelajarangeografi.